2016
DOI: 10.5551/jat.30965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Outcomes of Intracoronary and Intravenous Administration of Eptifibatide during Primary Percutaneous Coronary Intervention in Patients with Acute ST-Elevation Myocardial Infarction

Abstract: Aim: To compare the outcomes of intracoronary (IC) and intravenous (IV) administration of eptifibatide during primary percutaneous coronary intervention (PPCI) in patients with ST-elevation myocardial infarction (STEMI). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(59 reference statements)
1
3
0
1
Order By: Relevance
“…Esfandi et al studied 49 patients, 24 of whom received an intravenous high dosage bolus plus maintenance and 25 of whom received an intracoronary bolus. Gender, age, and other risk factors such as smoking, diabetes mellitus (DM), and high blood pressure were all non-significant in both groups [24], consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Esfandi et al studied 49 patients, 24 of whom received an intravenous high dosage bolus plus maintenance and 25 of whom received an intracoronary bolus. Gender, age, and other risk factors such as smoking, diabetes mellitus (DM), and high blood pressure were all non-significant in both groups [24], consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…E. Amir с соавт. [19] также сравнивали и/к и в/в пути введения эптифибатида у пациентов с ИМпST. Они установили, что и/к путь введения ассоциировался со значимым улучшением степени кровотока по TIMI, степени перфузии по TIMI, корректированной степени кровотока, оцененной по количеству кадров (TIMI frame count).…”
Section: Resultsunclassified
“…Our results were the same as the CICERO trial regarding the incidence of 30-day MACE (10% vs 6%, p=0.46), being higher in the I/V than the I/C group. I/C administration of eptifibatide during PPCI in patients with STEMI vs I/V administration of eptifibatide was evaluated in the study of E. Amir et al [19] and they found that I/C rout was associated with significantly better TIMI flow grade, TIMI perfusion grade, and corrected TIMI frame count and also secondary end points including LV ejection fraction, restoration of ST-segment elevation, and inhospital MACEs.…”
Section: Eptifibatid In Primary Pci эптифибатид при первичном чквmentioning
confidence: 99%
“…Furthermore, the appropriate route of administration of GP IIb/IIIa (intracoronary versus intravenous) is still debatable [5, 22–24]. IC eptifibatide was found to achieve better outcomes compared to conventional PCI and aspiration thrombectomy devices during primary PCI in STEMI patients [4].…”
Section: Discussionmentioning
confidence: 99%